Modeling of photovoltaic (PV) module temperature based on ambient factor in Malaysia using ANFIS - Wakiman, Nur Farhanah (2012)
This paper introduces a model build using Adaptive Neuro-Fuzzy Inference System (ANFIS) for evaluation of temperature for PV modules. The input of this model were taken from meteorological data which are ambient temperature,Ta, solar irradiation,GT, wind speed,Vw and humidity,RH. These parameters were evaluated from outdoor exposure data measured at Malaysia Green Technology Corporation (MGTC), Bandar Baru Bangi, Malaysia. The model was validated based on low training error and accepted validation error.